Tag-on-Demand: exploiting amber codon suppression technology for the enrichment of high-expressing membrane protein cell lines. Issue 10 (12th February 2019) - Britton, Zachary T; London, Timothy B; Carrell, Jeffrey; Dosanjh, Bhupinder; Wilkinson, Trevor; Bowen, Michael A; Wu, Herren; Dall'Acqua, William F; Marelli, Marcello; Mazor, Yariv
Abstract: Membrane proteins play key roles in the evolution of numerous diseases and as a result have become the most dominant class of targets for therapeutic intervention. However, their poor expression and detection oftentimes prohibit drug discovery and screening efforts. Herein, we have developed an approach, named 'Tag-on-Demand' that exploits amber suppression to control the expression of 'tagged' membrane proteins for detection and selections, yet can be turned off for expression of the protein in its native form. Utilizing an engineered Chinese hamster ovary cell line capable of efficient amber suppression, we evaluated the expression of a diverse panel of model membrane proteins and demonstrated the enrichment of cells with improved expression profiles, where 200–800% improvement in total protein expression levels were observed over pre-sorted populations after a single round of fluorescence-activated cell sorting. Furthermore, results were most striking for the typically difficult-to-express G protein-coupled receptor, CXCR2, where 2.5-fold improvement in surface expression was observed. We anticipate that the Tag-on-Demand approach will be suitable not only for membrane protein cell line development but also for the development of intracellular and secreted protein cell lines in expression systems for which amber suppression technology exists, including bacterial, yeast, insect and cell-free expression systems.